Intravitreal anti-VEGF Treatment in Central Retinal Vein Occlusion (CRVO): a Meta-Analysis of One Year Results - Gerding, H. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background It was the aim of this meta-analysis to assess the 12-month efficacy of intravitreal anti-vascular endothelial growth factor therapy in eyes with central retinal vein occlusion.Patients and Methods A MEDLINE-based survey was performed, including 33 publications (27 case series), covering a total of 1834 treated eyes. Baseline data (age, length of symptoms, visual acuity, gain in visual acuity at 3, 6, and 12 months) and average numbers of injections were calculated. Linear and non-linear regressions were calculated to relate baseline and treatment parameters and outcome. In a subgroup analysis, outcome data of randomised and non-randomised studies were compared.Results Mean gain in visual acuity was 2.8 ± 0.8 (mean±1 standard deviation), 2.7 ± 1.1 and 2.2 ± 1.4 lines at months 3, 6, and 12. 4.2 ± 1.2 and 6.4 ± 2.4 injections were given until months 6 and 12. Visual acuity gain improved significantly more in randomised trials (3.3 ± 0.7 and 3.0 ± 0.4, at months 6 and 12 versus 2.4 ± 1.1 and 2.2 ± 1.4, both p = 0.04) than in non-randomised studies. Eyes in randomised trials received significantly more injections (4.8 ± 1.1 and 8.6 ± 0.7 until month 6 and 12 versus 3.7 ± 1.0 and 5.6 ± 2.3, p = 0.045 and 0.04). After 12 months of care, the improvement in visual acuity was significantly correlating to the number of injections given. The dose response curve suggests saturation with treatment at an average of 7–8 injections within 12 months. The midpoint of the dose response curve was calculated at 6.78 injections per year.Conclusions The results of this analysis show that an improvement of approximately 3 lines can be maintained in the first year. Careful observation seems necessary to avoid under-treatment, which may occur below an average of 7–8 injections within the first 12 months of treatment.
Keywords: central retinal vein occlusion; CRVO; anti-VEGF; ranibizumab; aflibercept; bevacizumab; vascular endothelial growth factor; meta-analysis; review